Present State of Knowledge on the Orchids from Sarawak’s Peat Swamps - Magdalina, Stephen (Universiti Malaysia Sarawak (UNIMAS), 2022)
The orchid diversity and distribution at Sarawak’s peat swamps is considered to be understudied as most of the studies concentrate on mixed dipterocarp forests. Large areas of peat swamps in Sarawak have been threatened by uncontrolled anthropogenic activities causing the researcher difficult to collect data on orchids in disturbed areas. As a result, the current knowledge on the existence of peat swamp orchids becomes poorly understood. Hence, this study aimed to propose a provisional checklist of orchid species with their conservation status and distribution in the peat swamp areas of Sarawak. This study was conducted by collecting the information through the existing literature and documents from the internet and published books. The information on the subfamily, genus, species, habit, and distribution of the previous and currently recorded orchid species at Sarawak's peat swamp area were analysed and validated through the KEW World Checklist of Selected Plant Families. The inventory checklist of orchids in this study consists of 52 species and 26 genera from 3 subfamilies from Sarawak's peat swamps. Among the listed were classified into 42 epiphytes, eight terrestrials, and two myco-heterotrophs. Meanwhile, the present conservation status of the recorded peat swamp orchids was assessed via the IUCN Red List of Threatened Species and Malaysia Plant Red List. This study revealed that the peat swamp areas in Sarawak have become one of the most essential hotspots for orchid biodiversity and provide a deeper understanding of the current state of peat swamp orchids for future research.